Coping with Parental Death: Insights and Tips for Teenagers - Shreeve, Michelle (Rowman & Littlefield Publishers, 2022)
Losing a parent at any time in one’s life is difficult, but losing a parent when a teenager brings its own distinct challenges. Coping with Parental Death: Insights and Tips for Teenagers offers compassionate support for anyone struggling with the death of one or both of their parents. Through the stories of other teenagers who have lost a parent—as well as the author herself who lost her mother at a young age—you will see that you are not alone during this difficult time. You will learn Valuable coping methods Different ways to honor the memory of your loved one Strategies and advice from fellow teenagers How to navigate the first year and important milestones Tips for seeking out a counselor With expert advice, useful resources, relevant organizations, and even fictional movie references to provide additional perspective, Coping with Parental Death is a valuable guide to help you face the challenging road ahead with courage and care.